2013
DOI: 10.1016/j.metabol.2013.07.006
|View full text |Cite|
|
Sign up to set email alerts
|

Consuming a hypocaloric high fat low carbohydrate diet for 12 weeks lowers C-reactive protein, and raises serum adiponectin and high density lipoprotein-cholesterol in obese subjects

Abstract: Objective High fat, low carbohydrate (HFLC) diets have become popular tools for weight management. We sought to determine the effects of a HFLC diet compared to a low fat high carbohydrate (LFHC) diet on the change in weight loss, cardiovascular risk factors and inflammation in subjects with obesity. Methods Obese subjects (29.0–44.6 kg/m2) recruited from Boston Medical Center were randomized to a hypocaloric LFHC (n=26) or HFLC (n=29) diet for 12 weeks. Results The age range of subjects was 21–62 years. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 45 publications
3
89
5
1
Order By: Relevance
“…High-sensitivity CRP is the most sensitive assay for assessing CRP levels. 12 Usually, in apparently healthy subjects, CRP levels are lower than 3 mg l − 1 , but slightly increased levels can occur in normal individuals. These indicate a state of low-grade inflammation, which is frequently associated with obesity and metabolic syndrome, and predicts an increased risk of depression 13 and cardiovascular diseasescommon comorbidities in persons with SZ.…”
Section: Introductionmentioning
confidence: 99%
“…High-sensitivity CRP is the most sensitive assay for assessing CRP levels. 12 Usually, in apparently healthy subjects, CRP levels are lower than 3 mg l − 1 , but slightly increased levels can occur in normal individuals. These indicate a state of low-grade inflammation, which is frequently associated with obesity and metabolic syndrome, and predicts an increased risk of depression 13 and cardiovascular diseasescommon comorbidities in persons with SZ.…”
Section: Introductionmentioning
confidence: 99%
“…For example, even though subjects who followed a restricted carbohydrate diet started to regain weight after 6 months, the residual effects of carbohydrate restriction on blood lipids (HDL and triglycerides) levels were detectable for up to 2 years [15]. Another study that compared the effects of dietary macronutrient content (3.5% protein, 56.0% fat and 9.6% carbohydrate versus 22.0% protein, 25.0% fat and 55.7% carbohydrate) found that the high fat/low carbohydrate diet resulted in greater improvements in blood lipids and systemic inflammation when compared to the low fat/high carbohydrate, even though there were no detectable differences in body weight between the two diets [21].…”
Section: Lowering Cvd Risk: Will Only Weight Loss Do?mentioning
confidence: 99%
“…Additionally, a 12-week diet of high-fat, low-carbohydrate content (60% fat, 35% protein, and 40 g/day carbohydrates) led to greater improvements in blood lipid profiles by decreasing TG levels and increasing HDL cholesterol in comparison to a low-fat, high-carbohydrate diet (25% fat, 15% protein, and 60% carbohydrates; [21], which is in agreement with past work [14,15]. Conversely, additional groups have also reported increased levels of LDL cholesterol following low-carbohydrate and high-fat diets [16,22], whereas others reported initial increases in LDL cholesterol in individuals following diets low in carbohydrate content when compared to those following diets low in fat content, but there were no significant differences after 6 and 12 months follow-up [27].…”
Section: Lowering Cvd Risk: Will Only Weight Loss Do?mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of such diets on cardiovascular health has been the subject of intense investigation. Population studies evaluating the impact of HFLCD on cardiovascular clinical outcomes have provided a range of results, with some finding favorable changes in cardiovascular disease risk factors (9,35,37), and others showing an increased risk of adverse outcomes in both animal (29) and human studies, including in the setting of myocardial infarction (23). Consistent with this latter finding, we have previously demonstrated that HFLCD (when eaten prior to experimental infarction) induced lower recovery of cardiac function, larger infarct size, and increased risk of death by pump failure and ventricular arrhythmias following coronary ligation myocardial ischemia-reperfusion (25).…”
mentioning
confidence: 99%